Didi Kempot’s Campursari Songs: the Existence and the Effects of Communication Media - Putra, Noveryan Satria; Nurrohim, Novan; Nuryana, Ima; Pramudi, Yuventius Tyas Catur (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2022)
Indonesia is famous for its cultural heritage. Campursari is a musical genre of Indonesian local arts. Didi Kempot was a successful musician and singer who composed popular campursari songs. His songs were popular in Indonesia and abroad, such as in the Netherlands, Suriname, etc. The communication media greatly impacts the popularity of his works even though the maestro, Didi Kempot, has passed away. This research aims to examine the existence of regional arts and the effects of communication media on Didi Kempot’s Campursari music. Descriptive-qualitative method was applied in this research. The data were collected by observation on YouTube, Instagram accounts, 'Sobat Ambyar' fans, direct interviews with the Javanese cultural practitioners, and literature studies. The results of the study indicate that Didi Kempot’s campursari still exists today, although it undergoes decreased interaction in the community. Media Communication has also succeeded in influencing people's communication behavior to interact. This is because the development of media and technology makes it easier for the public and accelerates the dissemination of information.